1998
DOI: 10.1007/s005860050091
|View full text |Cite
|
Sign up to set email alerts
|

Vertebral end-plate (Modic) changes on lumbar spine MRI: correlation with pain reproduction at lumbar discography

Abstract: IntroductionVertebral end-plate (Modic) changes were first described independently by de Roos et al. [9] and Modic et al. [15] as being a feature associated with degenerative intervertebral disc disease. Type I changes consist of reduced signal intensity (SI) in the vertebral end-plates on T1-and increased SI on T2-weighted sequences (Fig. 1). They are associated with fissuring of the cartilaginous end-plate and increased vascularity within the subchondral bone marrow on histological examination. Type II chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
207
3
9

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 303 publications
(226 citation statements)
references
References 25 publications
7
207
3
9
Order By: Relevance
“…As such, Modic changes might be due to altered mechanical stress, resulting in histological changes, leading to signal intensity changes on MRI, namely the Modic changes. Biochemical causes on the other hand, imply that Modic changes may result from an inflammatory reaction to toxic mediators or infection from the degenerating disc [39]. An intervertebral disc herniation could be the entry point of bacteria into the disc, and the Modic changes could be therefore the result of anaerobic bacteria leading to oedema and inflammation surrounding the extruded intra-vertebral nuclear material [9,40].…”
Section: Discussionmentioning
confidence: 99%
“…As such, Modic changes might be due to altered mechanical stress, resulting in histological changes, leading to signal intensity changes on MRI, namely the Modic changes. Biochemical causes on the other hand, imply that Modic changes may result from an inflammatory reaction to toxic mediators or infection from the degenerating disc [39]. An intervertebral disc herniation could be the entry point of bacteria into the disc, and the Modic changes could be therefore the result of anaerobic bacteria leading to oedema and inflammation surrounding the extruded intra-vertebral nuclear material [9,40].…”
Section: Discussionmentioning
confidence: 99%
“…We found a similar trend: most (67%) hypointensities seemed to turn into hyperintensities or disappear, while most (65%) hyperintensities persisted or increased. It has been suggested that they may represent different consecutive phases of the degenerative process in the subchondral marrow [3,17]. The importance of the endplate [21,22] and subchondral bone [8] for the integrity of the intervertebral disc has been pointed out.…”
Section: Discussionmentioning
confidence: 99%
“…Subchondral signal abnormalities have been found to be associated with LBP [2,3,5,11,26], particularly with hypointensities [2,13,23]. Subchondral edema-like hypointensity on T1 weighted image (T1WI), being hyperintense on T2 weighted image (T2WI), has been found in association with vascularized fibrous tissue and with fissuring or disruption in the adjacent end plates [17].…”
Section: Introductionmentioning
confidence: 99%
“…By recreating the patient's pain, proponents of discography argue that it is more sensitive and specific than other imaging modalities, including plain radiographs, myelography, and MRI, which are known to identify both symptomatic and asymptomatic abnormalities. [2][3][4] However, critics question the reliability and specificity of discography since concordant pain has been suggested to originate from nonspine sources and can be reproduced in patients without any prior history of back pain. 5,8,11 A prospective study intended to evaluate the predictive value of provocative discography following lumbar fusion was performed by Carragee et al 7 Lumbar fusions were performed in 32 patients with presumed discogenic pain and a positive discogram (see Table 1).…”
Section: Scientific Foundationmentioning
confidence: 99%